An exploratory study on how the corruption level of the host country affects foreign direct investment’s inflows - Raso, Alessandra Aur (2016)
In today’s business world everything seems to be somehow linked to globalization, what leads to trading without barriers, developing productions schemes that involves more than one country and one location, capital flows and technology transfer. Foreign Direct Investment (FDI) has been used in the past decades as one of the main sources of capital to sustain cash flow needs for the globalization process. So how do investors decide where to invest? A number of risk factors are analyzed as part of this decision process, and among them is the level of corruption of the country of inflows destination. This exploratory study , based on quantitative and qualitative analysis, reviewed the relation between FDI inflows and the level of corruption in the host country to develop hypotheses and propositions that lead to complementary research to conclude on how and to which extend the level of corruption of the host country impacts its FDI inflows. In order to narrow down the universe explored, which would be to vast if all possible combinations of home and host countries were to be incorporated, the population used to perform analysis was based on Brazil’s and China’s data being the host country and its main FDI investors as home countries of the FDI inflows. Historical series of the indicators used in the quantitative analysis were obtained for the period from 2005 to 2012.